Basic rotordynamics : introduction to practical vibration analysis /: introduction to practical vibration analysis. ([2017]) - Matsushita, Osami, 1944-; Tanaka, Masato; Kanki, Hiroshi; (Executive engineer), Kobayashi, Masao; Keogh, Patrick
No abstract available